Multiple-Facet Diversity Patterns of Aquatic Vegetation in Lakes along a Trophic Gradient (2021)
Zervas, Dimitrios, Vasiliki Tsiaoussi, Athanasios S. Kallimanis, Panayotis Dimopoulos, Erwin Bergmeier, and Ioannis Tsiripidis. 2021. Multiple-Facet Diversity Patterns of Aquatic Vegetation in Lakes along a Trophic Gradient. Water 13, no. 16: 2281. https://doi.org/10.3390/w13162281